Equilibrium points in polymatrix games - Janovskaja, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Е. Б. Яновская. Ситуации равновесия в полиматричных играхE. Janovskaja. Polimatricinių lošimų pusiausvyros taškai